Pedagogical dialogic gatherings: giving a voice to the learning process of higher education students - Laorden Gutiérrez, Cristina (2021)
This article analyses the impact of Pedagogical Dialogic Gatherings (PDG) as a successful educational approach in a university context, thus favouring other learning methods that move away from traditional lectures. During four academic years, the interventions of 87 third year Social Education students have been analysed. On the one hand, a survey whose data were analysed quantitatively was created; on the other hand, the students’ accounts in the PDG sessions and in-depth interviews were qualitatively analysed and four categories of analysis were established. The results show how this method can contribute to the future professional activity of the students, providing them with the necessary tools to implement it in different social contexts. The results also show its contribution to the development of their critical and reflective capacity, to the relationship with the environment, to the promotion of models based on peer learning and to the reflections on reading. This article aims to provide some evidence of the PDG experience in higher education, therefore contributing to increase scientific data that support this successful method at this level of education.